Long-term integrated nutrient management drives physiological efficiency and yield gains in pearlmillet–wheat cropping system - Ahlawat, Vishal; Dadarwal, R S; Anita Kumari; Yadav, Parmod Kumar; Ramdhan Jat; Kautilya Chaudhary; Kavita; Pawan Kumar (The Indian Journal of Agricultural Sciences, 2026)
A long-term field experiment on integrated nutrient management in a pearl millet–wheat cropping system, established in 1985 at CCS HAU, Hisar provided the platform for this study. Observations were systematically recorded over three consecutive years, from 2021 to 2023. Long-term nutrient management practices critically influence soil health, crop physiological traits, and ultimately grain yield sustainability under semi-arid conditions. In this study, the impact of integrated nutrient management strategies on key physiological parameters—assimilation rate, transpiration rate, stomatal conductance, chlorophyll content, relative water content, and photochemical quantum yield—was evaluated for the pearl millet–wheat system. Treatments that combined inorganic fertilizers with organic sources such as farmyard manure (FYM), wheat straw, or green manure significantly enhanced physiological performance over fertilizer-alone treatments. For instance, the highest assimilation rates in pearl millet (20.4 μmol CO₂ m⁻² s⁻¹) and wheat (24.6 μmol CO₂ m⁻² s⁻¹) were recorded under the integrated nutrient regime with 50% N substituted by FYM, representing a 35–40% increase over the unfertilized control. Similarly, maximum stomatal conductance and relative water content were observed in treatments involving FYM and wheat straw combinations, reflecting improved water use efficiency and stress tolerance. Grain yield improvements were substantial: pooled yields in pearl millet increased from 1496.5 kg ha⁻¹ (control) to 3351.5 kg ha⁻¹ (50% N via FYM + 50% inorganic), while wheat yields rose from 1741 kg ha⁻¹ to 5107.5 kg ha⁻¹ under the same treatment, showing a remarkable 193% increase. Treatments involving partial substitution of chemical fertilizers with organics consistently maintained high yields, demonstrating the synergistic effect of integrated nutrient use. Overall, the study highlights that integrated nutrient management significantly enhances physiological efficiency and grain productivity in pearl millet–wheat systems, offering a robust pathway for sustainable intensification in semi-arid agro-ecosystems.